Hydrogel-Embedded Model Photocatalytic System Investigated by Raman and IR Spectroscopy Assisted by Density Functional Theory Calculations and Two-Dimensional Correlation Analysis - Geitner, Robert; Goetz, Stefan; Stach, Robert; Siegmann, Michael; Krebs, Patrick; Zechel, Stefan; Schreyer, Kristin; Winter, Andreas; Hager, Martin D.; Schubert, Ulrich S.; Gräfe, Stefanie; Dietzek, Benjamin; et al. (Journal of Physical Chemistry A, 2018)
The presented study reports the synthesis and the vibrational spectroscopic characterization of different matrix-embedded model photocatalysts. The goal of the study is to investigate the interaction of a polymer matrix with photosensitizing dyes and metal complexes for potential future photocatalytic applications. The synthesis focuses on a new rhodamine B derivate and a Pt(II) terpyridine complex, which both contain a polymerizable methacrylate moiety and an acid labile acylhydrazone group. The methacrylate moieties are afterward utilized to synthesize functional model hydrogels mainly consisting of poly(ethylene glycol) methacrylate units. The pH-dependent and temperature-dependent behavior of the hydrogels is investigated by means of Raman and IR spectroscopy assisted by density functional theory calculations and two-dimensional correlation spectroscopy. The spectroscopic results reveal that the Pt(II) terpyridine complex can be released from the polymer matrix by cleaving the C=N bond in an acid environment. The same behavior could not be observed in the case of the rhodamine B dye although it features a comparable C=N bond. The temperature-dependent study shows that the water evaporation has a significant influence neither on the molecular structure of the hydrogel nor on the model photocatalytic moieties.
CRIS-Team Scopus Importer:2023-04-20